Technology, design and process innovation in the built environment [ - Drogemuller, Robin; Hampson, Keith [ (Keith Douglas)]; Newton, P. W. [ (Peter Wesley)] , 1948- (Spon research, 2009)
Buildings and infrastructure represent principal assets of any national economy as well as prime sources of environmental degradation. This book incorporates the results of a major research programme